Level of quality of life and health self-care in university students of health sciences at the National University of Villa María - Romero, D. E. (2022)
The purpose of this study is the analysis of self - perceived quality of life and self-care of university students in their first years of Health Sciences Degrees at Instituto Académico Pedagógico de Ciencias Humanas (IAPCH) - National University of Villa María (UNVM). Methods: An observational, descriptive and correlational, cross-sectional design was implemented to conduct this study. It involved all the students in the first three years of the Medicine and Occupational Therapy degrees, with an estimated total of 280 students. The socio-demographics considered were: age, gender, origin and level of education of the immediate family members (father, mother and brother/sister). The Quality of Life assessment was carried out based on the SF-36 and the self-care assessment was performed according to the “Appraisal of the Capacity for Self-Care Agency Scale”. Results: Regarding quality of life, the Physical Component Summary (PCS) is higher than the Mental Component Summary (MCS) and with regard to the analysis based on gender, men revealed a higher perceived quality of life in both the physical and mental aspects. Women revealed a lower perceived quality of life regarding their physical functioning, emotional role, vitality, mental health, social role, bodily pain and general health. The analysis of self – care capacity showed that the total score in men and women corresponds to a medium level of self-care capacity, however, the highest proportion, in men as well as in women, was found in the category of low self-care capacity.